Achieving the sustainable development goals which include lowering inequality and poverty with financial inclusion - Huda Z. Miklif (Peerian Journals Publishing, 2025)
In recent years, the importance of financial inclusion in the global economy has grown, especially in light of advancements in communications technology, including digital financial technology, electronic payments, and mobile money services. A key instrument for attaining economic growth and development and raising standards of financial well-being is financial inclusion. Financial inclusion helps achieve a number of Sustainable Development Goals, such as lowering poverty, encouraging shared growth, achieving food security, offering high-quality education and health opportunities, and achieving gender equality, by offering financial services to people and communities without bank accounts. Financial inclusion has been positioned by several international financial institutions, including the World Bank, the International Monetary Fund, and the Consultative Group to Assist the Poor, as one of the key components for speeding development. The World Bank defines financial inclusion as the availability of a broad variety of financial services that address the needs of people and communities in an economical and sustainable way, including loans, savings accounts, payment accounts, insurance, and financial commodities. By making it possible for people to access and use financial services, financial inclusion makes a substantial contribution to the reduction of poverty and inequality. Research indicates a substantial correlation between financial inclusion and a decrease in inequality and poverty. People who have access to bank accounts and loans have the chance to boost their income and engage more fully in the economy. As a result, the gap between the affluent and the poor is lessened as new financial products facilitate the inclusion of underserved populations in the financial system. By offering technical assistance and creating strategic plans targeted at attaining financial inclusion at the local and national levels, several governments and international organizations try to put financial inclusion ideas into action. To sum up, financial inclusion is essential to reaching the Sustainable Development Goals, especially those pertaining to poverty and inequality reduction. To do this, nations must implement efficient plans based on their prior achievements.
Keywords: poverty; inequality; financial inclusion; ustainable Development